Improved electrochemical performance of onion-like carbon coated magnetite nanocapsules as electromagnetic absorptive anode materials for lithium-ion batteries. Issue 41 (7th May 2015) - Bi, Nannan; Liu, Xianguo; Wu, Niandu; Cui, Caiyun; Sun, Yuping
<x xml:space="preserve">Abstract</x> The synthesis of magnetite (Fe3O4)@C nanocapsules with Fe3O4 nanoparticles as the core and onion-like carbon as the shell has been reported.